2008
DOI: 10.1158/1078-0432.ccr-07-1954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of d-Methionine as a Novel Oral Radiation Protector for Prevention of Mucositis

Abstract: Purpose: Oral mucositis is a common acute morbidity associated with radiation and/or chemotherapy treatment for cancer. D-Methionine (D-Met), the dextro-isomer of the common amino acid L-methionine, has been documented to protect normal tissues from a diverse array of oxidative insults. Experimental Design: We evaluated if D-Met could selectively prevent radiation-induced oral mucositis using in vitro cell culture models as well as an in vivo model of radiation injury to the oral mucosa in C3H mice. Results: U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 57 publications
2
56
1
Order By: Relevance
“…⁎ p b 0.05, ⁎⁎ p b 0.001. and assumed that the binding would reduce the antitumor efficacy of the cisplatin. However Deegan et al (1994) clearly demonstrated that the cisplatin-methionine complex retains most of its cytotoxic activity against tumors which is consistent with the results of the testing in appropriate tumor models (Jones and Basinger, 1989;Cloven et al, 2000;Vuyyuri et al, 2008). Consequently, D-methionine appears to be an appropriate candidate for a clinical therapy to reduce the side effects of cisplatin therapy.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…⁎ p b 0.05, ⁎⁎ p b 0.001. and assumed that the binding would reduce the antitumor efficacy of the cisplatin. However Deegan et al (1994) clearly demonstrated that the cisplatin-methionine complex retains most of its cytotoxic activity against tumors which is consistent with the results of the testing in appropriate tumor models (Jones and Basinger, 1989;Cloven et al, 2000;Vuyyuri et al, 2008). Consequently, D-methionine appears to be an appropriate candidate for a clinical therapy to reduce the side effects of cisplatin therapy.…”
Section: Discussionsupporting
confidence: 63%
“…Further D-methionine does not interfere with the tumor kill of cisplatin in combination with radiation or radiation alone (Vuyyuri et al, 2008). These studies were appropriately designed and powered to determine if any statistically significant antitumor interference occurred and used tumor models for cancers commonly treated with cisplatin clinically including ovarian cancer (Cloven et al, 2000), carcinosarcoma (Jones and Basinger, 1989) and murine squamous cell carcinoma cells (Vuyyuri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interest in D-met as a radioprotector was spurred by reports that, in animal models, it could effectively prevent the oxidative stress-induced ototoxicity and nephrotoxicity associated with the chemotherapeutic agent cisplatinum (21,22). A recent report also documented radiation protection with D-met of primary nontransformed human cells (fibroblasts, keratinocytes, and endothelial cells) with a protective factor of 1.2 to 1.6 in clonogenic assays in vitro, whereas radiation protection was not observed in a panel of transformed human tumor cell lines in vitro or in vivo (23). Further, irradiation of the snouts of mice daily for 5 days resulted in mucositis compared with control animals, with a peak mucositis score of 3.5 ± 0.25 on a scale from 0 to 7 that was elevated compared with control animals (peak value, 0.4 ± 0.2; P < 0.001).…”
mentioning
confidence: 96%
“…D-Methionine treatment did not alter tumor control following cisplatin and radiation. Pharmacokinetics showed that liquid suspension of D-Methionine in rats had 68% bioavailability relative to IV administration (Vuyyuri et al, 2008). In a mouse model of radiation-induced mucositis, D-Methionine showed a dose-dependent increase in protection from mucositis.…”
Section: D-methionine and Tempolmentioning
confidence: 99%
“…In a mouse model of radiation-induced mucositis, D-Methionine showed a dose-dependent increase in protection from mucositis. Furthermore, D-Methionine did not compromise chemoradiationmediated tumor control (Vuyyuri et al, 2008). A phase I clinical trial was conducted to assess the pharmacokinetics of MRX-1024, the orally bioavailable formulation of D-Methionine, in healthy individuals and head and neck cancer patients undergoing radiation therapy and/or chemotherapy.…”
Section: D-methionine and Tempolmentioning
confidence: 99%